Antecedent and outcomes of human capital in enhancing service small- and medium-sized enterprises’ international performance - Ahmad, Norwan (2020)
This study is aimed at improving comprehension on the antecedent and outcomes of human capital in enhancing international performance of business service small- and medium-sized enterprises (SMEs) by drawing on the Dynamic Capability View, Resource-based Theory, and Institutional Theory. Essentially, human capital reflects the knowledge, skills, and abilities of individuals in a firm, which are key for enhancing international performance concerning success in foreign markets such as in terms of revenue, profit, and market share. Despite the importance of human capital in influencing performance as well as the fact that business service SMEs’ depend highly on human capital, investigations in the literature on the antecedents and outcomes of human capital on international performance is still limited. Investigation into the relationship between human capital and international performance is pivotal in light of the challenges facing Malaysian business service SMEs which suffer from weak international performance. This study proposes that managing human capital wisely may enhance SMEs’ capabilities and create innovative service offerings, which may contribute to better international performance. Also, the study suggests that one of the ways to develop human capital is through the adoption of a knowledge-based human resource management. A quantitative research method is employed involving a survey on 278 business service SMEs from Malaysia. Prior to conducting the quantitative study, a qualitative preliminary study was conducted to validate the factors that drive international performance found from the literature, which facilitate the development of the research framework. Four key findings were found from this study. First, knowledgebased human resource management was indeed an antecedent of human capital. Second, human capital was found to positively influence international performance. Third, dynamic capability in the aspects of entrepreneurial orientation, foreign market knowledge, marketing capability, and technological capability were found to mediate the relationship between human capital and innovative service offerings. Fourth, innovative service offerings and government facilitation were found to drive the international performance of business service SMEs. These findings point towards the importance of both, internal resources and capabilities, as well as external support from the government in ensuring international performance among business service SMEs. The study provided support for Resource-based Theory, Dynamic Capability View, and Institutional Theory. The study’s findings are beneficial for the stakeholders of the industry such as business service SMEs, government agencies, and trade associations.